Airbreathing Propulsion An Introduction - Bose, Tarit; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Airbreathing Propulsion covers the physics of combustion, fluid and thermo-dynamics, and structural mechanics of airbreathing engines, including piston, turboprop, turbojet, turbofan, and ramjet engines. End-of-chapter exercises allow the reader to practice the fundamental concepts behind airbreathing propulsion, and the included PAGIC computer code will help the reader to examine the relationships between the performance parameters of different engines. Large amounts of data on many different piston, turbojet, and turboprop engines have been compiled for this book and are included as an appendix. This textbook is ideal for senior undergraduate and graduate students studying aeronautical engineering, aerospace engineering, and mechanical engineering.
Preface -- 1. Introduction -- 2. Thermodynamic Ideal Cycle Analysis -- 3. Friction, Work and Heat Addition in a One-dimensional Channel Flow -- 4. Flow Through a Turbomachine -- 5. Estimating Losses -- 6. Similarity Rules (On Design Condition) -- 7. Axial Compressors and Turbines -- 8. Centrifugal Compressor -- 9. Off Design Running of Aircraft Gasturbines -- 10. Propeller Aerodynamics -- 11. Materials and Structural Problems -- List of Symbols -- Bibliography -- Index.
Keywords: Aerospace engineering; Astronautics; Thermodynamics; Fluid mechanics; Heat engineering; Heat transfer; Mass transfer; Aerospace Technology and Astronautics; Thermodynamics; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer